8-Mercaptoguanine-based inhibitors of Mycobacterium tuberculosis dihydroneopterin aldolase: synthesis, in vitro inhibition and docking studies - Alexia de Matos Czeczot; Candida Deves Roth; Rodrigo Gay Ducati; Kenia Pissinate; Raoní Scheibler Rambo; Luís Fernando Saraiva Macedo Timmers; Bruno Lopes Abbadi; Fernanda Souza Macchi; Víctor Zajaczkowski Pestana; Luiz Augusto Basso; Pablo Machado; Cristiano Valim Bizarro (Taylor & Francis Group, 2021)
The dihydroneopterin aldolase (DHNA, EC 4.1.2.25) activity of FolB protein is required for the conversion of 7,8-dihydroneopterin (DHNP) to 6-hydroxymethyl-7,8-dihydropterin (HP) and glycolaldehyde (GA) in the folate pathway. FolB protein from Mycobacterium tuberculosis (MtFolB) is essential for bacilli survival and represents an important molecular target for drug development. S8-functionalized 8-mercaptoguanine derivatives were synthesised and evaluated for inhibitory activity against MtFolB. The compounds showed IC50 values in the submicromolar range. The inhibition mode and inhibition constants were determined for compounds that exhibited the strongest inhibition. Additionally, molecular docking analyses were performed to suggest enzyme-inhibitor interactions and ligand conformations. To the best of our knowledge, this study describes the first class of MtFolB inhibitors.